Penguatan Budaya Literasi di SDN Desa Danau Sadar : Upaya Membangun Generasi Berkarakter melalui Literasi Sejak Dini - Herman Fland Dakhi; Novitasari Novitasari; Emy Rahayu; Devianna Hutasoit; Ellyn Purwanti; Niken Tri Handayani; Heri Frencus; Kevin G.P Aritonang; Vito Alamo; Natanael Kristanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study focuses on strengthening the culture of literacy at SDN Desa Danau Sadar as an effort to build a generation of character through early literacy. Reading literacy, introduction of literacy trees, and the school teaching program are the three main approaches implemented in this program. The results of the study showed a significant increase in students' reading and writing skills, as well as an increase in reading interest. The socialization of reading literacy succeeded in increasing parental awareness and participation in supporting literacy at home. The introduction of literacy trees motivated students to read more books and develop critical thinking skills. The school teaching program provided significant additional academic support, improving student achievement in core subjects. In conclusion, these programs succeeded in creating a conducive learning environment and supporting students' academic and character development.